2020
DOI: 10.1007/s42770-020-00350-w
|View full text |Cite
|
Sign up to set email alerts
|

Viral diversity in oral cavity from Sapajus nigritus by metagenomic analyses

Abstract: Sapajus nigritus are non-human primates which are widespread in South America. They are omnivores and live in troops of up to 40 individuals. The oral cavity is one of the main entry routes for microorganisms, including viruses. Our study proposed the identification of viral sequences from oral swabs collected in a group of capuchin monkeys (n = 5) living in a public park in a fragment of Mata Atlantica in South Brazil. Samples were submitted to nucleic acid extraction and enrichment, which was followed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The limited number of patients (only six samples each group) was the major limiation of this study. Although there were also studies performed based on samll sample size (Zeng et al, 2019;Dos Santos et al, 2020), we advocate that convincing conclusions can be proposed based on only large number of samples. In addition, potential influencing factors such as diet, lifestyle factors (such as socio-economic status and the attention to oral hygiene) that may influence oral microbiota composition were not considered, which may be confounding factors to the results.…”
Section: Discussionmentioning
confidence: 75%
“…The limited number of patients (only six samples each group) was the major limiation of this study. Although there were also studies performed based on samll sample size (Zeng et al, 2019;Dos Santos et al, 2020), we advocate that convincing conclusions can be proposed based on only large number of samples. In addition, potential influencing factors such as diet, lifestyle factors (such as socio-economic status and the attention to oral hygiene) that may influence oral microbiota composition were not considered, which may be confounding factors to the results.…”
Section: Discussionmentioning
confidence: 75%
“…As it is the sister group to Old World primates (OWP) (infraorder Catarrhini), including humans, the comprehension of their evolution, immunology and susceptibility to infectious diseases is central to the characterization of the scope of etiological agents that may impact global health 18 . In this sense, previous investigations have shown that multiple viral families might be found in the virome of NP: novel papillomaviruses were found infecting Callithrix penicillata 16 and Alouatta guariba 15 , anellovirus and genomovirus in Sapajus nigritus 10 , smacovirus in Alouatta caraya 12 and foamy virus in Brachyteles arachnoides 14 and Sapajus xanthosternos The Anelloviridae family is one of the most frequently found in metagenomic surveys of NP. This family is composed of non-enveloped virions with circular single-stranded negative sense DNA (ssDNA), whose genomes range from 1.6 to 3.9kb.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Neotropical primates (NP) (infraorder Platyrrhini) stand out as a group with great ecological importance, whose viral diversity hasn't been fully explored. Only 18% (4/22) and 3.4% (6/178) of NP genera and species, respectively, have been previously assessed through viral metagenomics 10,[12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations